Conformational choice and selectivity in singly and multiply hydrated monosaccharides in the gas phase. - Cocinero, E; Stanca-Kaposta, E; Scanlan, E; Gamblin, D; Davis, B; Simons, J (2008)
Factors governing hydration, regioselectivity and conformational choice in hydrated carbohydrates have been examined by determining and reviewing the structures of a systematically varied set of singly and multiply hydrated monosaccharide complexes in the gas phase. This has been achieved through a combination of experiments, including infrared ion-depletion spectroscopy conducted in a supersonic jet expansion, and computation through molecular mechanics, density functional theory (DFT) and ab initio calculations. New spectroscopic and/or computational results obtained for the singly hydrated complexes of phenyl beta-D-mannopyranoside (beta-D-PhMan), methyl alpha-D-gluco- and alpha-D-galactopyranoside (alpha-D-MeGlc and alpha-D-MeGal), when coupled with those reported earlier for the singly hydrated complexes of alpha-D-PhMan, beta-D-PhGlc and beta-D-PhGal, have created a comprehensive data set, which reveals a systematic pattern of conformational preference and binding site selectivity, driven by the provision of optimal, co-operative hydrogen-bonded networks in the hydrated sugars. Their control of conformational choice and structure has been further revealed through spectroscopic and/or computational investigations of a series of multiply hydrated complexes; they include beta-D-PhMan.(H2O)2,3, which has an exocyclic hydroxymethyl group, and the doubly hydrated complex of phenyl alpha-L-fucopyranoside, alpha-L-PhFuc.(H2O)2, which does not. Despite the very large number of potential structures and binding sites, the choice is highly selective with binding invariably "focussed" around the hydroxymethyl group (when present). In beta-D-PhMan.(H2O)2,3, the bound water molecules are located exclusively on its polar face and their orientation is dictated by the (perturbed) conformation of the carbohydrate to which they are attached. The possible operation of similar rules governing the structures of hydrogen-bonded protein-carbohydrate complexes is proposed.